Assessment of PCDD/F risk after implementation of emission reduction at a MSWI - Lee, Se-Jin; Choi, Sung-Deuk; Jin, Guang-Zhu; Oh, Jeong-Eun; Chang, Yoon-Seok; Shin, Sun Kyoung (Chemosphere (Oxford), 2007)
Municipal solid waste incinerators (MSWIs) have been shown to be important sources of polychlorinated dibenzo- p-dioxins and dibenzofurans (PCDD/Fs). The emission of PCDD/Fs by MSWIs is a controversial subject in human health risk assessment. In this study the effect of a MSWI on a residential area was assessed before and after the installation of an additional treatment system for flue gas. This additional treatment system resulted in a dramatic decrease in PCDD/F concentrations in stack flue gas samples by 99.98%, while the concentrations in air decreased by approximately 50% (36,500 and 0.75 pg I-TEQ m −3 for air in 1999; 3.5 and 0.38 pg I-TEQ m −3 in 2002; 1.6 and 0.076 pg I-TEQ m −3 in 2005 for stack gas and air, respectively). Considering the congener distributions of PCDD/Fs between stack flue gas and air samples, the study area seemed to have been contaminated by other urban sources as well as the MSWI. ISC3 model results support the conclusion that this incinerator became only a minor contributor to the study area after installation of the supplementary systems. This resulted from both proper MSWI operation using modern technology and additional sources of contaminants in this region. Finally, PCDD/F uptake by humans through inhalation of contaminated air was estimated. Assuming that inhalation exposure contributes 10% of total exposure, total exposure was lower than WHO guidelines. These results confirm that proper operation and maintenance of the incinerator led to a reduction in emissions and potential health impacts of PCDD/Fs.